2017
DOI: 10.1097/prs.0000000000003763
|View full text |Cite
|
Sign up to set email alerts
|

Craniosynostosis Surgery: Does Hospital Case Volume Impact Outcomes or Cost?

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…However, the specific details about life-threatening and catastrophic events were not reported. 6 Our study assessed the occurrence of life-threatening and catastrophic events during the surgical treatment of patients with complex craniofacial conditions at a single high-volume pediatric craniofacial unit. Fortunately, these Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the specific details about life-threatening and catastrophic events were not reported. 6 Our study assessed the occurrence of life-threatening and catastrophic events during the surgical treatment of patients with complex craniofacial conditions at a single high-volume pediatric craniofacial unit. Fortunately, these Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There are several recently published studies detailing complications following pediatric craniosynostosis surgery. [4][5][6][7][8] In 2017, the Pediatric Craniofacial Surgery Perioperative Registry assessed 1223 cases from 31 institutions across the United States from June 2012 to September 2015 and presented a comprehensive overview of the perioperative management, outcomes, and intraoperative complications, which included cardiac arrest (0.2%), hypotension (5.3%), bradycardia requiring treatment (1.6%), suspected venous air embolism (1.1%), and large-volume (>40 mL/kg) blood transfusion (26.8.1%) but no deaths. 8 This study highlighted the large variability in perioperative management and outcomes and opportunities for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…When examining patient costs and hospital volume, this study found that patient admission charges related to orthognathic operations at high-volume hospitals were significantly less than other hospitals ( P <0.001). This trend has been seen in various general surgery and plastic surgery procedures 23–26 . However, when analyzing other craniofacial procedures, a national study on cleft palate repair was unable to demonstrate associations between hospital volume and costs 27 .…”
Section: Discussionmentioning
confidence: 99%
“…This holds true across the literature for other surgical procedures, including various general surgical procedures, cardiac surgical procedures, overall microsurgical procedures, free flap breast reconstructive surgery, craniosynostosis surgery, and orthognathic surgery. 1,[24][25][26]28 Highvolume hospitals experiencing fewer surgical complications could be because of surgeon experience, established multidisciplinary teams, and optimized care pathways for these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as this subspecialty has matured, numerous advances in anesthetic and blood conservation techniques have taken place, along with many technical improvements, which have together significantly reduced associated morbidity and mortality rates. 72–78…”
mentioning
confidence: 99%